High Prevalence of Intimate Partner Violence Against Women in Young Adulthood: Is Prevention Failing? - Gracia Trinidad, Enrique (Journal of interpersonal violence, 2023)
In the last decades, prevention measures have been taken globally to reduce the high prevalence of intimate partner violence against women (IPVAW) in our societies. As a consequence, a gradual reduction in the prevalence of IPVAW in the younger generations should be expected. However, international prevalence data suggest that this is not the case. In the present study, we aim to compare IPVAW-prevalence rates across age groups in the adult population in Spain. We used data from the Spanish 2019 national survey based on 9,568 interviews with women, reporting IPVAW in three time periods: lifetime, the last 4 years, and the last year. To ensure accurate comparisons of IPVAW-prevalence rates across age groups, we first examined the psychometric properties, and measurement invariance of the set of questions addressing the different types of IPVAW (i.e., physical, sexual, psychological) in this survey. Results supported a three-factor latent structure addressing psychological, physical, and sexual IPVAW, showing high-internal consistency and validity evidence. For lifetime prevalence, the youngest age groups (18–24 years) were those with the highest latent mean in psychological and physical IPVAW, with those aged 25 to 34 years having the highest score in sexual IPVAW. Women aged 18 to 24 years showed the highest factor scores in the three types of violence during the last 4 years and during the last year. A number of potential explanatory hypotheses are proposed to better understand the high prevalence of IPVAW among younger generations. The reason why IPVAW prevalence remains alarmingly high among young women, despite the preventive measures taken in recent years, is a research question that remains open. Prevention efforts should target younger generations if IPVAW is to be eradicated in the long term. However, this goal will only be achieved if those prevention efforts prove to be effective.